Lobbying and the Power of Multinational Firms - Andreas Polk; Armin Schmutzler; Adrian Müller (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Can multinational firms exert more power than national firms by influencing politics through lobbying? To answer this question, we analyze the extent of national environmental regulation when policy is determined in a lobbying game between a government and firm. We compare the resulting equilibrium regulation levels, outputs and welfare for national and multinational firms, depending on such parameters as the potential environmental damages, transportation costs and the influence of the firm. For low transportation costs, output and pollution of a national firm is always as least as high as for a multinational; this changes for high transportation costs and intermediate damage parameters. When there is no lobbying, welfare levels are always higher with multinationals than with national firms. However, the existence of lobbying may reverse this ordering.
Keywords: D72; F23; L51; 330